ACTUALIZING THE MORAL VALUES OF THE TA'LIM AL-MUTA'ALLIM TO SHAPE STUDENTS' RELIGIOUS BEHAVIOR: A CASE STUDY AT MTSI ATTANWIR BOJONEGORO - Fudla Afiyati; Muhammad Walid; Mulyono (STKIP Citra Bakti, 2026)
Moral education plays a crucial role in shaping the religious behavior of students amidst rapid technological advancements and social changes. This study aims to analyze the actualization of moral values ??derived from the Ta’lim al-Muta’allim in shaping the religious behavior of ninth-grade students at MTs Islamiyah Attanwir Bojonegoro, as well as to identify supporting factors, inhibiting factors, and the resulting implications. The study employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and subsequently analyzed using the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing. The results indicate that the actualization of moral values ??is manifested through the cultivation of habits regarding conduct toward Allah SWT (performing acts of worship and religious activities), conduct toward teachers (demonstrating respect, politeness, and diligence in learning), and conduct toward others (showing mutual respect, helpfulness, and maintaining harmony). Supporting factors include student motivation, teachers serving as role models, family support, and a religious *madrasa* environment, whereas inhibiting factors include external environmental influences, social media, limited facilities, and a lack of student consistency. The actualization of these moral values ??has implications for both the outward conduct and inner character of the ninth-grade students at MTs Islamiyah Attanwir Bojonegoro.